Functional and structural liver abnormalities in former PCB exposed workers–analyses from the HELPcB cohort - Kaifie, Andrea; Schettgen, Thomas; Gube, Monika; Ziegler, Patrick; Kraus, Thomas; Esser, André (Journal of Toxicology and Environmental Health-Part A-Current Issues, 2019)
The effects of polychlorinated biphenyls (PCB) on liver function and structure are still under debate. Although higher transaminase activity and tumor promoting potential of PCB reported for animal and human studies was suggested, these studies were not able to provide definitive evidence on the ability of these chemicals to affect liver function and contribution to tumor development. The aim of this study was to determine the influence of PCB on liver function and morphology in a cohort of former PCB exposed workers. Over 5 years, a longitudinal analysis of the association between PCB concentration and hepatic transaminases such as alanine transaminase (ALT) aspartate amino transaminase (AST) and gamma glutamyltransferase (γGT), as well as liver size and structure was undertaken. Data demonstrated a significant inverse association between PCB concentration and γGT activity levels but there was no marked relationship with AST and ALT activities. Regarding sonographic examination, a significant association was found between liver size and PCB concentration. This association remained, even after adjusting for alcohol consumption, liver affecting drugs, timespan of internal exposure, or age. No marked correlation was noted between PCB concentration and liver structure changes. In summary, an association was observed between PCB concentration and γGT activity levels as well as liver size in humans. The long-term health consequences attributed to PCB on liver and in particular in tumorigenesis are not foreseeable in our cohort thus far, but remain a focus in further ongoing surveillance.
CRIS-Team Scopus Importer:2023-09-25
Keywords: cohort study; Liver transaminases; occupational exposure; persistent organic pollutants; POP